Nasaan Ka, Pawi?: Co-Creating a Child-Informed Storybook for Early Childhood Sustainability Education - Rendel B. Batchar; Blessilda Grace C. Tigas (Indonesian Journal on Education (IJoEd), 2026)
Early Childhood Education for Sustainability (ECEfS) is gaining prominence as a foundational approach to nurturing environmental awareness and behavior among young learners. However, instructional materials are often adult-constructed, with limited incorporation of children's perspectives. Anchored in a design-based research (DBR) framework, this study documents the second phase of a project exploring the environmental consciousness of 39 kindergarten pupils in a laboratory school in Central Luzon, Philippines. Building on a previously published visual-semiotic analysis of children’s environmental drawings, this paper focuses on the thematic analysis of their verbal narratives about environmental protection. Using Braun and Clarke’s six-phase approach, two core themes emerged: (1) Cultivation, Appreciation, and Care of Nature, and (2) Waste Management Awareness and Responsible Disposal. These themes reflected early eco-literacy and surfaced misconceptions (e.g., equating flower-picking or feeding wild animals with protection). The insights informed the iterative design and development of a localized green instructional resource—a storybook titled Nasaan ka, Pawi?—which was published and launched during the 2024 Pawikan Festival in collaboration with the Provincial Tourism Office of Bataan. This study demonstrates how DBR can be used to co-create culturally resonant and developmentally appropriate learning materials grounded in children’s lived experiences, advancing the goals of Education for Sustainable Development (ESD) in early childhood.